Preparation and properties of alkali-activated slag-like powder paste - Donghui Li; Wenzhong Zheng; Ying Wang (Journal of Materials Research and Technology)
To address the challenges of transporting cementitious materials during the construction of islands and reefs in remote seas, local materials like sea sand and calcium carbonate-rich coral reefs were considered for preparing slag-like powder (SP), and alkali-activated slag-like powder paste (AASPP) was obtained by activating SP with alkaline activators. This study used sea sand and ground calcium carbonate powder as raw materials to prepare five types of SP with different Ca/Si (C/S) ratios by melting, water quenching, and grinding. Liquid sodium silicate (LSS) served as the activator for SP in preparing AASPP with fluidity ranging from 144 to 200 mm, final setting time from 48 to 2272 min, and compressive strength at 28 days reaching up to 135.72 MPa, achieving the strength level of alkali-activated slag paste (AASP). The effects of the silicate modulus (Ms) and Na2O content (Nc) in LSS, and the C/S ratio in SP on the fluidity, setting time, and strength development of the AASPP were also explored. Additionally, a series of analytical techniques, including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electronic microscopy with energy dispersive spectroscopy (SEM-EDS), were used to explain the underlying reasons for the differences in macroscopic properties from a microscopic perspective. Finally, a Ms of 1.8 and a Nc of 8% were selected as the optimal mix proportion of the LSS-activated SP paste.